Edukasi 10 Indikator Perilaku Hidup Bersih dan Sehat (PHBS) Tatanan Rumah Tangga di SMA Korpri Kota Banjarmasin Tahun 2020 - Norfai Norfai; Eddy Rahman; Khairul Anam (Jurnal Abdimas Kesehatan (JAK), 2020)
The purpose of this community service activity is to increase students' knowledge about the 10 indicators of Clean and Healthy Behavior household arrangements. Counseling uses media power points, but before starting counseling, questionnaires are filled out by students (pretest). Counseling is carried out by lecture, discussion and question and answer methods, then after counseling, the questionnaire is distributed again to be filled out by students (posttest), after knowledge data before and after counseling has been obtained, then the data analysis using Wilcoxon statistical test. Based on the results of community service activities at the KORPRI senior high school in Banjarmasin, the p-value (0,000) <α (0.05) means that there is a significant difference in knowledge between before and after counseling using power point media, thus it can be concluded that the counseling method uses media power point conducted at the KORPRI senior high school in the city of Banjarmasin is able and successful in increasing students' knowledge about the 10 indicators of Clean and Healthy Behavior  household arrangements. It is recommended that schools can work together with the Public Health Services in the region in order to empower school health unit (UKS) to be able to educate school health unit members who are tasked with providing health education using the media, especially power point media in order to help provide comprehensive understanding for other students about health through school health unit at the KORPRI senior high school in Banjarmasin.